GEMS: which galaxies dominate the z~0.7 ultraviolet luminosity density? - Wolf, C; Bell, E; McIntosh, D; Rix, H; Barden, M; Beckwith, S; Borch, A; Caldwell, J; Haeussler, B; Heymans, C; Jahnke, K; Jogee, S; et al. (Institute of Physics Publishing, 2004)
We combine high-resolution images from GEMS with redshifts and spectral energy distributions from COMBO-17 to explore the morphological types of galaxies that dominate the z~0.7 UV luminosity density. We analysed rest-frame 280 nm and V-band luminosities of 1483 galaxies with 0.65